Oral health disparities in early childhood and intergenerational gaps among noncitizen migrants, Arabs, and Jews in South Tel Aviv, Israel - Jonathan Brill; Adi Vinograd; Barak Hermesh; Rivka Sheffer; Zohar Mor (International Journal for Equity in Health)
Abstract Introduction Disparities in oral health are related to dental care knowledge, domestic oral hygiene practices and socioeconomic status. This cross-sectional study aimed to compare the oral hygiene and dental care practices of migrant, Arab, and Jewish children residing in Tel Aviv, Israel, and assess the influence of parental dental practices. Methods Data were collected from parents of children aged 3 to 6 years. Parents completed their own and their children’s oral health status, oral hygiene practices, dietary habits and dental care knowledge. Results Of the 504 children, 153 (30.4%) were migrants, 117 (23.2%) were Arabs, and 234 (46.4%) were Jews. Twice-daily tooth brushing was reported by 57.5% of migrant children, 47% of Arab children, and 63.7% of Jewish children (p = 0.001). Compared with Arab and Jewish children, migrant children had higher rates of tooth filling and urgent dental interventions under general anesthesia (22.9%, 11.1%, and 9%, respectively; p < 0.001). The parent‒child association for twice-daily tooth brushing was strong overall (69.8%), particularly among migrants (70.9%) and Jews (72.3%), but weaker among Arabs (63.0%), p < 0.01. Conclusion Migrant children exhibited better tooth brushing habits than Arab children did but required more urgent dental interventions, highlighting gaps in preventive care. The strong parent‒child link in oral hygiene, particularly among migrants and Jews, suggests that culturally sensitive, family-focused interventions could help reduce these disparities and improve dental health outcomes for underserved populations.